2023
DOI: 10.1017/wsc.2023.49
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective of education in weed science

Taseer Ahmad,
Khawar Jabran,
Zahid Ata Cheema
et al.

Abstract: In modern agriculture, weed problems are predicted to worsen and become more complicated as a result of increasing invasiveness, herbicide resistance, and emphasis on high-input methods. Weeds cause huge economic yield losses that range from US$100 million to US$26 billion globally. The knowledge of weed science has offered success in the past through effective, reasonably priced, and secure technologies; specifically, synthetic herbicides to effectively control weeds in agroecosystems. Weed science is accepte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The decreased yield losses show improved weed control that, aids the plants to consume more growth resources while increasing yield loss in control perhaps extreme opposition of weeds. This is consistent with the observations of Abbas et al (2018) and Ahmad et al (2023) who concluded the smallest yield loss was gained where the lowest weed crop opposition to nutrients and water happened.…”
Section: Grain Yieldsupporting
confidence: 93%
“…The decreased yield losses show improved weed control that, aids the plants to consume more growth resources while increasing yield loss in control perhaps extreme opposition of weeds. This is consistent with the observations of Abbas et al (2018) and Ahmad et al (2023) who concluded the smallest yield loss was gained where the lowest weed crop opposition to nutrients and water happened.…”
Section: Grain Yieldsupporting
confidence: 93%
“…Weeds are defined as any undesired plant and are considered one of the main challenges in agricultural fields (Ahmad et al., 2023; Ghanizadeh & Harrington, 2019). Despite agricultural weeds exhibiting a distinct set of traits, most of them tend to present increased aboveground biomass in response to nutrient inputs (Little et al., 2021), quickly encroaching on pastures.…”
Section: Introductionmentioning
confidence: 99%